The Role of Agricultural Extension on Rationalizing Irrigations Water at Alhania region- Elgabal Elakhadar - Libya - Emragea, Mageda Rizig; Ferkash, Mohammad. E. (Journal of Pure & Applied Sciences, 2021)
in rural area. Objectives of this Research were to : 1- Measurement the degree of knowledge, attitude and practice of traditional irrigation farmers and developed irrigation farmers related to rationalization methods of irrigation water usage and determine differences between them. Determine the most factors affecting to knowledge, attitudes and practices of traditional irrigation farmers and developed irrigation farmers about rationalizing methods of irrigation water usage.2-Identify farmer's information sources in irrigation.3-Determine the most important problems, which face traditional irrigation farmers and developed in the field irrigation. To achieve the objectives of the research, data were collected by personal inter from a sample of (210) farmers (130 developed irrigation farmers & 80 traditional irrigation farmers). Data were collected through questionnaire with personal interview, for data analysis, percentages, averages standard  deviation and" t" test were used to determine differences between averages of the respondents values, simple correlation coefficient were used for data analysis. The main of the research revealed that : 1-There were significant differences between traditional and developed irrigation's farmers regarding knowledge attitudes and practices degree of rationalization methods of irrigation water usage.  2 -Knowledge of traditional irrigation and developed farmers about rationalization methods of irrigation water usage and factors affecting it.3-Practices of developed & traditional irrigation's farmers to rationalization methods of irrigation water usage, and factors affecting it.4 -Attitudes of traditional irrigation developed farmers and towards rationalization methods of irrigation water usage.